2020
DOI: 10.3390/polym12030589
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Effect of Molecular Chain Displacement and Carrier Trap Characteristics on DC Breakdown of HDPE/LDPE Blend Insulation

Abstract: This work focuses on the coupling effect of molecular chain displacement and trap characteristics on direct current (DC) breakdown properties of high density/low density polyethylene (HDPE/LDPE) blend insulation. Frequency domain spectroscopy (FDS) and isothermal discharge current (IDC) are used to characterize the dielectric relaxation and trap characteristics of HDPE/LDPE blends. A DC breakdown model is proposed to reveal the mechanisms of the molecular chain displacement and carrier trap on the DC breakdown… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 43 publications
0
12
0
Order By: Relevance
“…Thus, by extrusion mixing, it is possible to obtain a multimodal PE, which combines several polymers with different molecular weights, different degrees of branching and density. The importance of this area of research is confirmed by unrelenting attention to mixed compositions based on polyolefins and, in particular, polyethylene [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, by extrusion mixing, it is possible to obtain a multimodal PE, which combines several polymers with different molecular weights, different degrees of branching and density. The importance of this area of research is confirmed by unrelenting attention to mixed compositions based on polyolefins and, in particular, polyethylene [ 3 , 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The coefficients used in the BCT model were obtained from previous experimental studies, such as electron and hole mobility, deep trap energy and density, and injection barrier height that varies with temperature [ 24 , 25 , 26 , 27 ]. In particular, we assumed that deep trap energy has a single level for simplicity in this numerical analysis model.…”
Section: Analysis Of Space Charge Transport and Electric Field Distributionmentioning
confidence: 99%
“…With space charge analysis development, studies measuring the breakdown strength and analyzing the mechanisms have been conducted as the critical factor for stability and reliability. The breakdown strengths of polymeric insulators have been studied using numerical and statistical experimental approaches [ 24 , 25 , 26 , 27 ]. There are several models to interpret the breakdown mechanisms inside the polymeric insulators, such as the electro-mechanical model, electron avalanche model, molecular chain displacement model, and phase-field model [ 1 , 27 , 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, there is a relation between chain segment motion and space charge buildup where less restricted chain motion allows for more charging. [ 30 ] These factors explain both the differences between individual samples and between sample types, as LDPE would be less restricted in chain motion than XLPE and differences in the degassing temperature would also lead to different results.…”
Section: Tsdc Spectra Of D‐xlpe and Degassed Ldpementioning
confidence: 99%
“…Instead, net homocurrent arises from a combination of interface states and charge injection, which differences being due to factors such as restricted chain motion in XLPE preventing chain scission and void formation that promotes space charge buildup. [ 30 ] This restriction originates from the greater cross‐link density in XLPE, which reduces the motion of charged chain fragments that move due to the applied heat and electrical field. There was no meaningful difference in the obtained activation energies on average between the two types of samples, however, degassing temperature appeared to influence how far charges were able to migrate through the sample during poling for XLPE by altering these interface states, which influenced the resulting discharge current.…”
Section: Tsdc Spectra Of D‐xlpe and Degassed Ldpementioning
confidence: 99%